ANALYSIS OF TOLLING THE I. CLASS ROADS IN THE SR FROM REGIONAL POINT OF VIEW (Perner's Contacts, 2010)
The paper deals with e-tolling of the I. class roads in relation to national roadfreight transport. Article analyses e-tolling differences from regional point of view.It investigates the possibilities of II. class roads usage for regional haulage asalternative to the I. class usage.
Keywords: e-toll; national road freight transport; I. class roads; II. class roads